2017
DOI: 10.1186/s12933-017-0577-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CD14++CD16+ monocytes on plaque vulnerability in diabetic and non-diabetic patients with asymptomatic coronary artery disease: a cross-sectional study

Abstract: BackgroundPreviously, we have reported that daily glucose fluctuations could affect coronary plaque vulnerability, but the underlying mechanisms remained unclear. This study sought to investigate the impact of CD14++CD16+ monocytes on plaque vulnerability, as assessed by virtual histology intravascular ultrasound (VH-IVUS), as well as their relationship to fluctuating glucose levels in patients with asymptomatic coronary artery disease (CAD).MethodsFifty-one patients with asymptomatic CAD, who were undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…The fibro-fatty percentage was significantly lower with a corresponding higher necrotic core in the DM group. This relative variation in plaque composition is strongly associated with blood glucose fluctuations, as described previously by Yoshida et al [16].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The fibro-fatty percentage was significantly lower with a corresponding higher necrotic core in the DM group. This relative variation in plaque composition is strongly associated with blood glucose fluctuations, as described previously by Yoshida et al [16].…”
Section: Discussionsupporting
confidence: 57%
“…The changes in high-sensitivity C-reactive protein (hs-CRP) correlate with the increase in necrotic core and dense calcium percentage, along with the decrease in fibrous tissue in diabetic patients [15]. Studies have shown the association of a higher necrotic core in DM patients and greater glucose fluctuations [16]. IVUS studies have reported a 16–66% incidence of plaque rupture, TCFA being a precursor, in patients with ACS [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Additional differences between the DM and non-DM patients included a higher glucose variability in DM patients leading to an increase of plaque burden and lipid content and a decrease of fibrous tissue in their atherosclerotic plaques [ 43 ]. Yoshida et al [ 44 ] described an increase of necrotic core in plaque with DM patients with higher glucose fluctuations. We found a notable correlation of both baseline and follow-up glycemia with plaque burden in the DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…These coronary lesion characteristics favor plaque instability and degradation, and predict future major adverse cardiac events independent of myocardial ischemia [ 15 ]. Previous studies have revealed that glucose fluctuations provoke oxidative stress that leads to endothelial cell dysfunction, progression of coronary atherosclerosis, and plaque vulnerability [ 16 , 17 ]. These results suggest that there may be a symbiotic relationship between vulnerable plaque and T2DM.…”
Section: Potential Mechanisms Of Impaired Collateral Growth In Diabetmentioning
confidence: 99%